2020
DOI: 10.1155/2020/3739129
|View full text |Cite
|
Sign up to set email alerts
|

An Assistance to Project Risk Management Based on Complex Systems Theory and Agile Project Management

Abstract: Project Risk Management is crucial in determining the future performance of a complex project. Increasing project complexity makes it more and more difficult to anticipate potential events that could affect the project and to make effective decisions to reduce project risk exposure. To tackle these conceptual and managerial issues, the proposed approach introduces Complex Systems Theory-based improvements into some PRM subprocesses and runs the global PRM process using Agile Project Management principles. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…This concept is adopted from the project risk term, which is defined as “ an uncertain event or condition that, if it occurs, has a positive or a negative effect on a project objective .” 19 From normative rational theory, risk in project could be positive (opportunities) or negative (threats). 169,170,171,172,173 Positive challenges are associated with “opportunities” that could be gained from complexity aspects, and negative challenges are related with the “loss” from complexity condition. For instance, due to limited experience, several megaproject teams or stakeholders in developing countries often under uncertain conditions for structural aspect in the technology are to be applied.…”
Section: Resultsmentioning
confidence: 99%
“…This concept is adopted from the project risk term, which is defined as “ an uncertain event or condition that, if it occurs, has a positive or a negative effect on a project objective .” 19 From normative rational theory, risk in project could be positive (opportunities) or negative (threats). 169,170,171,172,173 Positive challenges are associated with “opportunities” that could be gained from complexity aspects, and negative challenges are related with the “loss” from complexity condition. For instance, due to limited experience, several megaproject teams or stakeholders in developing countries often under uncertain conditions for structural aspect in the technology are to be applied.…”
Section: Resultsmentioning
confidence: 99%
“…erefore, it is of great significance to identify logistics risks and correctly evaluate the reduction ratio of different logistics risks in order to optimize the resources where the most obvious benefits can be obtained. e research on project risks is helpful in making effective decisions to reduce the degree of construction project risk exposure [12]. In the current wave of globalization, there are a wide range of risks associated with international construction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A challenge to be considered, according to [12], is local government debt as a major problem in China's financial operations for a long time, and it has also become a key problem that seriously affects the financial risk of governments in any country. e construction of the local government debt risk assessment system should be based on the analysis of the government debt situation, and the risk assessment results should reflect the level of local government debt risk and help the local government to find and resolve risks in a timely manner [13]. According to [14], it is concluded that e-government directly affects the participation of citizens in budget documents and indirectly affects the increase of control, transparency, and accountability.…”
Section: Introductionmentioning
confidence: 99%